191 EXPRESSION OF ZAP-70 IS ASSOCIATED WITH DIFFUSE PATTERN OF BONE MARROW INVOLVEMENT IN PATIENTS WITH CHRONIC LYMPHOCYTIC LEUKEMIA. (1st January 2006) - Singh, J.; Huang, C.; Mathur, S.; Pabla, M.; Mayo, M.; Smith, H.; Williamson, S.
Abstract : Background: Intracellular zeta-associated protein of 70 kD (ZAP-70) is a surrogate marker of mutational status of immunoglobulin heavy chain variable region (IgVH) genes in chronic lymphocytic leukemia (CLL) cells. Both ZAP-70 and unmutated IgVH gene status has been associated with the presence of poor prognosis and overall poor survival. The pattern of bone marrow (BM) infiltration is another important prognostic factor in CLL. Patients with diffuse infiltration tend to have advanced disease and relatively poorer outlook, whereas nodular and interstitial patterns (may be grouped together and termed "nondiffuse ") is associated with less advanced disease and a better prognosis. The correlation between expression of ZAP-70 and pattern of BM infiltration is not known. We conducted a retrospective study to investigate the association between these two prognostic factors in CLL. Methods: Twenty-four consecutive patients, median age 68 (range 43-86) years, with CLL diagnosed between June 2002 and June 2005 underwent analysis of ZAP-70 expression and histological evaluation of iliac crest BM at initial diagnosis. All patients were Rai stage 0-2. Flow cytometric analysis of ZAP-70 was performed on either peripheral blood or BM aspirate using a Beckman Coulter Epics XL machine. BM aspirate and biopsy specimens were reviewed by a hematopathologist who was blinded to patient and disease characteristics. Histological pattern of BM involvement by CLL was classified into one of four categories: nodular (12%), interstitial (41%), mixed (17%), or diffuse (30%). Results: Diffuse BM histology was detected in 7 (29%) and nondiffuse histology was seen in 17 (71%) patients. Seven (29%) patients were ZAP-70 positive while ZAP-70 was not detected in 17 (71%) patients. Five of seven (71%) patients with diffuse BM pattern were ZAP-70 positive compared to only 2/17 (12%) with nondiffuse pattern (p = .008). All patients with diffuse BM involvement and 5/7 (71%) patients who were ZAP-70 positive had disease progression. Conclusions: Expression of ZAP-70 is associated with diffuse pattern of BM involvement in CLL. Peripheral blood analysis for ZAP-70 can be a surrogate marker for prognostic information provided by BM histology and could obviate the need for BM biopsy in newly diagnosed CLL. Larger studies are needed to validate our observations before routine use of ZAP-70 analysis can be advocated for this indication.